Response of Soybean Grown on a Claypan Soil in Southeastern Kansas to the Residual of Different Plant Nutrient Sources and Tillage - D. W. Sweeney; P. Barnes; G. Pierzynski (Kansas Agricultural Experiment Station Research Reports, 2020)
The residual from previous high-rate turkey litter applications, which were based on nitrogen (N) requirements of the previous grain sorghum crop, increased 2019 soybean yield more than that obtained from the residual of phosphorus (P)-based turkey litter applications (low rate) or the control. Even though early soybean growth was unaffected by residual treatments, the dry matter production at the R6 growth stage was greater with N-based litter application than with P-based applications or the control.
Keywords: turkey litter; fertilizer; residual; soybean yield